Bandage contact lens for in-game corneal abrasion can allow immediate return to play - Rohan Kubba; Ganesha R. Kandavel; Ganesha R. Kandavel; Ganesha R. Kandavel; Joshua Scott; Joshua Scott; Cesar Roldan; Hayden Jackson (Frontiers Media S.A., 2024)
While the prevailing treatment for corneal abrasions outside the athletic sphere is the application of a bandage contact lens (BCL), which lessens pain and allows for the maintenance of binocular vision, this is not the case during athletic play. This brief report highlights the advantage of BCLs in treating in-game corneal abrasions, ultimately allowing for an immediate return to play. Additionally, this report summarizes the mechanisms of bandage contact lenses, differentiates them from standard hydrogel contact lenses, and highlights the significant steps necessary to apply the bandage contact lens during an in-game corneal abrasion event. Overall, we link modern ophthalmology clinical practice and sports medicine, allowing for the attenuation of acutely-induced ocular pain to a manageable state.